(untitled) (International Journal of Agricultural Research, Innovation and Technology, 2018)
The study of soil physico-chemical properties were made on the soils of BuleHoraWoreda, WestGuji zone. The objective of the study was to characterize soil physical and chemical properties to assess the fertility status of the soils in the study areas. Soil profile pits at representative sites were described and soil samples were collected from each depth of 0-15 cm, 15 – 30 cm, and 30–60 cm depending on the root depth of the crop. Soil samples were collected from two different study areas for the determination of soil texture, bulk density, porosity, soil pH and electrical conductivity. The top layer (0-15 cm) has an average bulk density of 1.10 g/cm3, whereas the subsurface layer (15-30 and the bottom layer (30-60 cm) has an average bulk density of 1.16 g/cm3 and 1.26 g/cm3, respectively at the GuyyeKebele. The average value of bulk density 1.18 g/cm3, 1.29 g/cm3 and 1.39g/cm3 was recorded on the surface horizon (0-15 cm), subsurface horizon (15-30 cm) and the bottom horizon (30 - 60 cm) depth, respectively at BuleHora Farm. Accordingly, the highest (1.39 g/cm3) and the lowest (1.10 g/cm3) average bulk density values were recorded for BuleHoraand GuyyeKebele study Farm, respectively. The average highest porosity (58.48%) value was observed in the surface horizon (0 -15 cm) soil depth and the average lowest porosity value (52.11%) was observed in the bottom horizon (30 – 60 cm) depth at GuyyeKebele study Farm. The average porosity value of the soils in BuleHora study Farm were recorded 55.27%, 52.39% and 47.63% for the surface horizon (0 -15 cm), sub surface horizon ( 15 –30 cm) and bottom horizon (30 – 60 cm) depth , respectively. The soil textural class was changed with depth from sandy clay in surface horizon (0-15 cm) to clay in both sub surface horizon (15- 30 cm) and bottom horizon (30-60 cm) at GuyyeKebele. The pH value was observed on the soils of the GuyyeKebele study area increased from 6.08 at surface horizon (0 – 15 cm) to 6.27 at the sub surface horizon (15- 30 cm) and then slightly decreased to 6.21 at the bottom horizon (30-60 cm) of the soil depth. Lowest soil pH value (5.44) was measured in the surface horizon (0 –15 cm) and the highest pH value (6.09) was observed in bottom horizon (30-60 cm) soil depth at BuleHora farm. The electrical conductivity of the saturated soil paste extracts of the study area was low (ranging from 0.0387 to 0.1587 dS m-1) throughout the profile showing no significant accumulation of soluble salts to convert the soil to saline soil. Int. J. Agril. Res. Innov. & Tech. 7 (2): 43-48, December, 2017